Batik Go Digital: Transforming Msmes In Malang City Through Financial Literacy And Lamikro In The Indonesia Malaysia Partnership - Ratnawati, Ratnawati; M. Taufiq Noor, Rokhman; Esy Suraeni , Yuniwati; Ayu Agus Tya, Ningsih; Tasnim Nikmatullah, Realita; Norizah Mohd, mustamil (PT Inovasi Pratama Internasional, 2025)
This community service program aims to improve the capacity of batik MSMEs in Malang City to face the challenges of the digital era. Through a cross-border collaborative approach, this activity focuses on financial literacy assistance based on the LAMIKRO (Micro Accounting Report) application as a simple, effective financial recording tool that is tailored to the needs of MSMEs. The strategic partnership between Indonesia and Malaysia serves as a catalyst for the exchange of knowledge, technology, and best practices in micro-enterprise management. The results of this activity indicate an increased understanding of MSMEs regarding the importance of financial recording, as well as their readiness to utilize digital technology to expand market access and increase the competitiveness of local batik products. One of the problems faced by MSMEs is a lack of knowledge regarding professional financial management, so assistance on financial literacy is needed. One focus of management is financial literacy, understanding the use of digital finance, which helps MSMEs learn to record digital financial transactions (such as cash and bank, sales, purchases, and expenses) more easily and efficiently. The implementation of financial digitalization is one effort to improve the financial performance of MSMEs that can be measured so that it has an impact on their business development and financial stability.